The Master of Library Science graduates of the University of the Philippines Institute of Library Science a follow up study - Monroy, Corazon B.; Picache, Ursula G.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1982)
This study is a survey of the graduates of the Master of Library Science degree of the Institute of Library Science, University of the Philippines, for the years 1966-1980. Sixty-one out of 110, the total number of graduates, responded to a questionnaire intended to gather data for the study the main purposes of which are to know the types of jobs the UPMLS graduates are engaged in and to determine the factors related to their job satisfaction and dissatisfaction. The survey also aims to obtain feedback about the relevance of the course to the graduates' jobs and at the same time to determine the phase/phases of the course which should be improved such that it may render more effective service to the students. In addition it aims to ascertain the number of graduates not engaged in library work and their reasons for leaving the field.
It was found out that forty-six out of sixty-one respondents are presently in the field of librarianship and are occupying professional positions. Twelve respondents are presently out of the field; they shifted to other kinds of endeavor. The primary reason of those in the field for staying on is that they find their work interesting and rewarding. However, they answered that poor administrative support and low salary are the most probable causes for them to leave librarianship. On the other hand, various reasons for shifting to non-library work were enumerated by the twelve who have left the field. For one, they stated that the library profession has a poor image in terms of actual work and social status; secondly, it has a lower prestige and lesser recognition; and thirdly, it provides less opportunity for professional growth. There were only a few, however, who said that they were dissatisfied with their former work as librarian.
The foremost reasons of the respondents for taking the MLS are for professional growth and to obtain promotion. The most common expectation of the respondents after finishing the MLS course is "to receive a higher salary than what regular librarians usually receive". Majority of the respondents are satisfied with the MLS program; only three are not satisfied with the program. About 85 percent reported that the MLS program had prepared them well for their present job while about 15 percent reported otherwise. Library Administration, Cataloging and Classification, and Reference and Bibliography are the subjects the graduates consider most relevant to their present job. Many of them recommended the offering of other subjects such as: computer applications in libraries, indexing and abstracting techniques, public and human relations in libraries and others.
Based on the survey findings, it was concluded that most of the graduates are satisfied with certain job elements such as salary, working environment, participation in seminars, administrative involvement and work output but they feel dissatisfied with some elements like promotion, recognition and library budget. The MLS program has helped majority of the graduates to be more prepared for their jobs. In addition, the graduates have expressed high satisfaction in their assessment of the relevance and adequacy of the program, with the curriculum offering rated most highly, followed by methods of teaching. However, there is less satisfaction with the facilities.
The Institute has succeeded in its primary objectives for it has trained library administrators and it has also trained library educators. While majority of the respondents are satisfied with the MLS program, the following recommendations are shared both by the respondents and the researcher to improve the program. Practicum is a must especially for full-time non-library science student to put in practice what they learned theoretically and implement a more practical approach in the teaching of subjects.
Invite experts/specialists in information science and library science to lecture or teach in the Institute. This was emphasized by the graduates who had taken library science in their undergraduate course. Otherwise, they find the subjects boring and just a repetition of what they had taken in college. Provide more scholarships for Filipino librarians both locally and abroad to help librarians/information specialists cope with the latest trends in the field and help them become specialists in their area of concentration. Offer more workshops, seminars, and training programs for librarians and information specialists. There is a need for librarians particularly library administrators to support and enhance librarianship.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman. Institute of Library Science -- Alumni; University of the Philippines Diliman. Institute of Library Science -- Graduate Students